Synthesis, Docking, Computational Studies, and Antimicrobial Evaluations of New Dipeptide Derivatives Based on Nicotinoylglycylglycine Hydrazide - Khalaf, Hemat S. (Molecules, 2020)
Within a series of dipeptide derivatives (5–11), compound 4 was refluxed with d-glucose, d-xylose, acetylacetone, diethylmalonate, carbon disulfide, ethyl cyanoacetate, and ethyl acetoacetate which yielded 5–11, respectively. The candidates 5–11 were characterized and their biological activities were evaluated where they showed different anti-microbial inhibitory activities based on the type of pathogenic microorganisms. Moreover, to understand modes of binding, molecular docking was used of Nicotinoylglycine derivatives with the active site of the penicillin-binding protein 3 (PBP3) and sterol 14-alpha demethylase’s (CYP51), and the results, which were achieved via covalent and non-covalent docking, were harmonized with the biological activity results. Therefore, it was extrapolated that compounds 4, 7, 8, 9, and 10 had good potential to inhibit sterol 14-alpha demethylase and penicillin-binding protein 3; consequently, these compounds are possibly suitable for the development of a novel antibacterial and antifungal therapeutic drug. In addition, in silico properties of absorption, distribution, metabolism, and excretion (ADME) indicated drug likeness with low to very low oral absorption in most compounds, and undefined blood–brain barrier permeability in all compounds. Furthermore, toxicity (TOPKAT) prediction showed probability values for all carcinogenicity models were medium to pretty low for all compounds.